OECD Study of Cross-National Differences in the Treatment, Costs and Outcomes of Ischaemic Heart Disease - Moïse, Pierre (OECD Publishing, 2003)
The Ageing-Related Diseases study compares treatment trends and health outcomes on a disease-by-disease basis. Most of the day-to-day decisions that determine health care system performance are made in treating specific diseases. Therefore, the ARD's bottom-up approach to comparing health care system performance at the disease level, rather than the more common top-down approach, goes to the heart of health care system performance. This paper presents such an analysis for ischaemic heart disease. There is considerable variation in treatment trends for the same diseases across countries and much of this variation can be explained by differences in structural characteristics of health care systems. A disease-level analysis begins with an examination of these characteristics: the economic incentives, policies and regulations that affect individual providers' decisions for treating a specific disease, defining a particular health care system's approach. In order to properly assess ...
Keywords: Social Issues/Migration/Health